IMPLEMENTATION OF THE SALES SYSTEM IN INDUSTRIAL ENTERPRISES, ITS ESSENCE AND DIRECTIONS - Baqoeva Dilfuza (Scholar Express Journals, 2024)
The article on the implementation of the sales system in industrial enterprises, its essence and directions, provides information about the analysis and development of the sales systems that are important for enterprises. The thesis describes sales systems related to economic and other indicators of industrial enterprises. The thesis provides information about the components of sales systems, their importance, and their importance for enterprises.
Keywords: industrial enterprises; sales; trade; consumer